Double metal–insulator transitions and magnetoresistance properties in La0.8Na0.2−x□xMnO3 oxides. Issue 5 (April 2016) - Wali, M.; Skini, R.; Khlifi, M.; Bekri, M.; Dhahri, E.; Hlil, E.K.
Abstract: The electrical and magnetoresistance behavior of L a 0.8 N a 0.2 − x □ x M n O 3 (0.00≤ x ≤0.15) polycrystalline sample was investigated. Resistivity measurements versus temperature under different magnetic fields were performed to investigate the electronic transport and magnetoresistance properties. The abnormal transport properties were induced by the sodium deficiency content, characterized by the double metal–insulator transitions ( T P 1 and T P 2 ). The present results have been discussed and possible explanations given based on the related theory and previous reported results. The conduction mechanism was explained by the adiabatic small polaron hopping (ASPH) in the insulating region and by the competition between the small-polaron and spin-wave scattering in the metallic region. Moreover, a resistivity minimum has been observed for all samples in the temperature range from 2 to 70 K, which is strongly influenced by an applied magnetic field explained by a Kondo-like scattering mechanism. Therefore, the percolation theory is introduced to understand the transport mechanism in the whole temperature range. Hence, the estimated values of the resistivity was found to be in good agreement with the experimental data. Magnetoresistance measurements show high values reaching 60% for x =0.15 sample.